2014
DOI: 10.1155/2014/631756
|View full text |Cite
|
Sign up to set email alerts
|

Gabapentin in Acute Postoperative Pain Management

Abstract: Gabapentin (1-aminomethyl-cyclohexaneacetic acid) is an amino acid that has the structure of the neurotransmitter γ-aminobutyric acid (GABA). It is a novel drug used for the treatment of postoperative pain with antihyperalgesic properties and a unique mechanism of action. Gabapentin and the related, more potent compound pregabalin have been shown to be beneficial in the treatment of neuropathic pain as well as postoperative pain following spinal surgery and hysterectomy. This study reviews five aspects of gaba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
73
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(79 citation statements)
references
References 55 publications
1
73
0
5
Order By: Relevance
“…In a study using gabapentin for hysterectomy pain, PONV was more common in the control group than in the treatment group. Studies have revealed that gabapentin reduces PONV [8,30]. In our study, there was no significant difference in the incidence of vomiting between the two groups, while nausea was 50% less frequent in the treatment group 6-11 h postoperatively, which is consistent with other studies [8,21].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In a study using gabapentin for hysterectomy pain, PONV was more common in the control group than in the treatment group. Studies have revealed that gabapentin reduces PONV [8,30]. In our study, there was no significant difference in the incidence of vomiting between the two groups, while nausea was 50% less frequent in the treatment group 6-11 h postoperatively, which is consistent with other studies [8,21].…”
Section: Discussionsupporting
confidence: 92%
“…Gabapentinoid drugs have relatively mild side effects, but high doses can cause dizziness, sedation, nausea, loss of balance, lower limb edema, urinary retention, constipation, and pruritus [11,12,30]. Several studies using gabapentinoids for acute postsurgical pain have reported PONV.…”
Section: Discussionmentioning
confidence: 99%
“…2 Opioids are used during perioperative period in several patients. 3,4 The limitations of opioids include their side effects. Also not all patients respond well to opioids.…”
Section: Introductionmentioning
confidence: 99%
“…Как в наших наблюдениях, так и по данным литературы у этих пациентов сущес-твенно быстрее купировались симптомы общемозгового синдрома. Длительность и интенсивность общемозгового синдрома яв-ляется основным содержанием клинических проявлений лёгкой и среднетяжёлой череп-но-мозговой травмы, и его скорейшая коррек-ция -важная задача лечения при черепно-мозговой травме [4]. ВЫВОДЫ 1.…”
unclassified
“…Применение габапен-тина перед операцией служит эффективным методом контроля предоперационной тре-вожности. Установлено, что применение га-бапентина после тиреоидэктомий позволяет блокировать позднюю послеоперационную боль [4].…”
unclassified